Bamboo : The Multipurpose Plant - Akinlabi, Esther Titilayo; Anane-Fenin, Kwame; Akwada, Damenortey Richard (Springer International Publishing : Imprint: Springer, 2017)
This book is intended for use both in the industry and the academia. It introduces the physical, chemical and the mechanical properties as well as the characterization of bamboo. Novel industrial applications in structural, non-structural, reinforcement, afforestation, land reclamation, environmental significance, textile, medical, geotechnical, hydraulic, food, Pulp and the paper industries are addressed in detail. Bamboo has been used for centuries as a structural material as well as in diverse engineering applications, food and medicinal purposes, especially in Asia. As a natural fiber composite, bamboo has the potential for many developments in academic and industrial research. Current literature on composites tends to focus on bamboo as a plant or solely as a structural engineering material. This book seeks to bring together these two extremes and provides a holistic resource on the subject.